The Effect of Marketing Mix on Patient Loyalty: Study at Dental and Oral Hospital in Wetlands - Ika Kusuma Wardani; Rosihan Adhani; Fatimah Maulideya; Fatma Kirana (Malahayati Nursing Journal, 2024)
ABSTRACT Based preeliminary research survey, more than 50% of patients in RSGM Gusti Hasan Aman were integration patients. The purpose is other cluster patients such as patients who come to the polyclinic and also specialist patients will also increase significantly such as visits by integration patients, and they will become loyal patients to the hospital. The aims of this study is to analyze the effect of marketing mix on patient loyalty. This study uses a type of analytic observational research. The research design used was cross sectional. The population in this study were all patients who had been outpatient at RSGM Gusti Hasan Aman. The number of samples in this study were 67 patients consisting of general patients and BPJS patients. The sampling technique used is a non-probability sampling technique, namely purposive sampling. The instrument used in this research is a questionnaire. Most of the respondents are loyal, have a good perception of the service. The results stated price (p value = 0.555), place (p value = 0.906) and promotion (0.818) had no significant effect on general patient loyalty. Meanwhile, product (p value = 0.035), people (p value = 0.012), process (p value = 0.020), and physical evidence (p value = 0.035) have a partially significant effect on patient loyalty. Conclusion: Marketing mix has an effect of 55.6% on general patient loyalty and BPJS at the Gusti Hasan Aman Dental and Oral Hospital. The rest is influenced by other factors. Keywords: Marketing Mix, Patient Loyalty, Wetlands, Public Patients, BPJS